2006
DOI: 10.1158/1055-9965.epi-05-0664
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Carotenoids, Retinoids, and Tocopherols in the Serum and Buccal Mucosa of Chronic Cigarette Smokers versus Nonsmokers

Abstract: Background: Cigarette smoking, a major risk factor for oropharyngeal cancer, is reported to alter oral levels of carotenoids and tocopherols. Such effects may be important because these nutrients, as well as retinoids, are putative chemoprotective agents. Objectives: To determine whether chronic smoking is associated with altered concentrations of these nutrients in serum and buccal mucosa; to distinguish whether such effects are ascribable to diet; and to determine whether oral concentrations of these nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
2
40
1
1
Order By: Relevance
“…The high incidence of low vitamin C concentrations in BMC may be due to a methodical error in the sample processing. In line with others [11,28,30], we found significantly high positive correlations between the AOX concentrations in blood plasma and BMC for vitamin E and ß-carotene.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high incidence of low vitamin C concentrations in BMC may be due to a methodical error in the sample processing. In line with others [11,28,30], we found significantly high positive correlations between the AOX concentrations in blood plasma and BMC for vitamin E and ß-carotene.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the determination of their concentrations at the main site of action, namely, the buccal mucosal cells (BMC) as in this study, could be more reliable [8,11].…”
Section: Introductionmentioning
confidence: 98%
“…However, these protective effects of carotenoids may not necessarily be exerted on lung tissues in the smoking human. Indeed, plenty of studies have documented potentially harmful effects of carotenoids on lung outcomes, with increased risk for lung cancer and mortality in heavy smokers [1519]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been said that at least 200 substances that are toxic to the biological system have been isolated from tobacco smoke [6]. The buccal cell concentration of the carotenoids, retinoids, and the tocopherols were generally lower among the heavy smokers versus the light smokers [29], which increases the susceptibility of periodontal disease and they may be the reason for the higher incidence of periodontal disease in the smokers group. Cross-sectional studies have consistently shown the higher prevalence, extent, and severity of various periodontal disease outcomes in smokers than in non-smokers [30,31].…”
Section: Discussionmentioning
confidence: 99%